The state of students argumentative writing: An ai-assisted qualitative inquiry into the implementation of a toulmin-based teaching model - Farous Izwan Abdul Aziz; Jason Miin-Hwa Lim; Seriaznita Mat Said (Global Academic Excellence, 2024)
Students in Malaysia. As these students are only introduced to the genre in their upper secondary years, they encounter challenges due to the complexity of the discourse, which persists even at the tertiary level. This study aims to investigate whether the implementation of a Toulmin-based teaching model could improve the students’ argumentative writing skills. By analysing degree-level students’ essay samples, the researchers attempted to highlight the common weaknesses of the students so as to indicate how a Toulmin-based writing model could be rightly used as a pedagogical tool. Essay samples provided by 76 undergraduate ESL students from a public university were analysed to identify the presence of Toulmin’s argumentative elements while a rubric was used to review their organisation, content and language skills. Our findings show that students were able to aptly present a basic argumentative structure even though they still struggled with relatively advanced components. Despite the students’ ability to present a clear structure, their essays lacked depth, supporting evidence and explicit logical links. Apart from showing signs of plagiarism, the students also exhibited weaknesses in organisation, grammar, vocabulary and translation competency. The results show that a structured argumentative writing framework is needed to help students improve their writing abilities via a set of critical thinking skills, particularly in the process of composing increasingly sophisticated arguments.